Foreign aid in areas of limited statehood - Dreher, Axel; Lang, Valentin; Ziaja, Sebastian (CESifo working papers, 2017)
We review the aid effectiveness literature to assess whether foreign aid given to areas of limited statehood can be expected to promote economic and social outcomes in the recipient country. We distinguish different types of aid, motives for granting it, recipient country policies and characteristics, and modalities by which aid is delivered, as these factors have been argued to influence the effectiveness of aid. In short, aid is most likely to be successful if given for non-strategic motives, and if given to recipient countries with "good" policies and democratic institutions. Fragmented aid and aid amounts that exceed the absorptive capacity of the recipient reduce the effectiveness of aid. We then compare these properties between recipients most affected by limited statehood and those least affected. This allows us to assess the relative effectiveness of aid in countries with areas of limited statehood. We conclude that on average aid given there is less likely to be effective than elsewhere.
Keywords: Arbeitspapier; Graue Literatur